(untitled) (Research, Society and Development, 2023)
The infection by Sars-CoV-2 represents an aggression to the whole organism and has the respiratory system as a gateway. Most children who come into contact with the virus develop milder cases, but severe cases quickly progress to septic shock, refractory metabolic acidosis, coagulation dysfunction and/or acute respiratory distress syndrome (ARDS) may occur. Respiratory physiotherapy acts from milder cases to more aggressive cases, with physiotherapeutic techniques being important to alleviate the sequelae of COVID-19. With this, the study aimed to analyze which physiotherapeutic treatments are most efficient in combating COVID-19 and add more knowledge to the scientific community. This is an integrative literature review, carried out by manual search in the databases, Scientific Electronic Library Online (Scielo), Web of Science and National Library of Medicine (PubMed/ Medline), Latin American and Caribbean Literature in Health Sciences (Lilacs). The initial sample contained 163 contents, however, after countless analyzes, only 9 articles were selected. After reviewing the studies, it was observed that the pediatric population presented less aggravations when infected by the virus, being more likely to manifest severe conditions, mostly children who already had preexisting diseases. Physiotherapeutic resources were extremely important both in reducing the exacerbation of the disease and in combat, considerably improving the situation of these children. The main treatments used in this public were: oxygen supplementation, invasive mechanical ventilation (IMV), positioning and early mobilization.